Application of GPR During Investigation Concerning Causes of Pavement Failure and Road Subgrade Quality in Granitoid Massif Near Simtany - Kovář, Luděk; Pospíšil, Pavel (GeoScience Engineering, 2013)
The survey of damaged engineering buildings is in many cases very demanding in terms of the selection of a right exploration method in relation to the results obtained for subsequent engineering works, time for survey implementation, and violations arising from survey activities. Heterogeneity of materials of a natural and anthropogenic origin is a fundamental axiom which can subsequently lead to either a distortion or a failure threatening statically the existence of a building structure. On the test object of a pavement, after some time of its use, severe deformations became evident whose causes and future evolution were not known. Within the design of survey techniques being able to quickly and efficiently uncover the causes of failures, the GPR (Ground Penetrating Radar) investigation was included which as an indirect, non-destructive survey method very quickly helped to clarify he causes of failures of the building structure.